A review of the Pomerantziidae (Acari: Prostigmata: Pomerantzioidea), with the description of a new genus - Fan, Qing-Hai; Chen, Yan (Zootaxa, 2005)
The family Pomerantziidae is reviewed and the genus Pomerantzia Baker is redefined. A new genus Apomerantzia is established for two described species, A. kethleyi (Price, 1975) comb. n. and A. prolata (Price, 1971) comb. n., formerly placed in Pomerantzia. Keys to stages and species of the family are provided. An Oriental species, P. subterranea sp. n. collected from deep soil in Fuzhou, China is described and illustrated. The family is recorded in China for the first time.